ENSURING THE ECONOMIC DEVELOPMENT OF THE COUNTRY BY DEVELOPING THE CAPITAL MARKET - Saidov Khabibulla Shavkat ogli (Galaxy International Interdisciplinary Research Journal, 2023)
In recent times Ensuring the economic development of the country by developing the capital market. The argument that economies may be lagging and that the capital markets may not be providing the needed impetus for financial intermediation and economic progress has been put forward by few number of researchers.